The Epigraphic and Archeological Work of Nikola Vulić on the Territory of Macedonia - Ljubomirović, Irena V. (Collection of Papers of the Faculty of Philosophy in Priština, 2018)
This work is a result of decades long archaeological excavations by Nikola Vulić on the territory of Macedonia. The work also comprises of his compilation of epigraphic monuments. During the systematic excavations on numerous sites in Macedonia, Vulić achieved significant results which served as a base for future projects. His work on Greek and Roman epigraphy has been fundamental for understanding the ancient history of the Balkan Peninsula. The paper also presents the newest results.
Keywords: Nikola Vulić; archaeology excavations; epigraphic monuments; ancient settlements